Accountability and level of competency of the Shariah Supervisory Board in Bank Muamalat Malaysia Berhad - Mohamad Yunus, Mohd Hadli Shah (2016)
The establishment of Islamic banking and finance is prevailed by Shariah principles. In this regard, it is important to have a comprehensive, robust and well-functioning Shariah audit and governance to guarantee that all products and services offered by the Islamic Financial Institutions (IFIs) are widely acknowledged as Shariah compliant. The purpose of this study is to examine the role played by Shariah Supervisory Board (SSB) of an IFI in ensuring the accountability conception and the level of auditing competency is consistent with the Shariah principles. The focus of the study is on aspects of three issues, which are: Shariah compliance, accountability and level of auditing competency. In this study, the qualitative research method was applied and ethnographic research approach was employed so as to understand the social context on the accountability and level of competency amongst SSB. The data gathering process included three sources of empirical materials. First is through Bank Muamalat Malaysia Berhad’s (BMMB’s) website, newsletter and other publicly accessible materials. Second is by inconspicuous on-site observation: by participation in meetings, planning sessions and in other internal gatherings. Third is through observations and informal conversations supplemented by semi-structured interviews with the key respondents represented by the members of Shariah Committee (SC) and Shariah Department staff of BMMB Head Office for a period of two months. The findings of this study primarily revealed that the SSB members deal in accordance with regards to the Shariah compliance comprehension in association with IFI interpretation and accountability conception. This study also found that the epistemological conception of accountability emphasises on the subjection, transparency, independence, confidentiality, faith and justice which reflects the relationship between self and statutory regulations are positively influenced by Islamic business ethic. Hence, the association of accountability and level of auditing competency has a significant influence in supporting SSB supervising the IFI accordingly. This study will definitely contribute to a practical conceptual framework of solutions to the IFI. At the same time, it may contribute a full range of knowledge and skills to the standard setter in determining the problems, designing and implementing suitable remedial measures. In addition, it will benefit the educational institutions in Malaysia especially in the development of curriculum and training modules for Shariah audit that fulfill the Shariah requirements. The educational institutions must also take up the challenge to produceable and certified Shariah auditors’ graduates to cater for thefuture demand globally. Furthermore, the findings of this research may be used as guidelines and evaluation for future references.